Extremism in Education in Pakistan: University Teachers’ Thoughts - Nauman A. ABDULLAH; Muhammad SAEED (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi, 2016)
This research study was conducted to explore the teachers’ thoughts on extremism in education in Pakistan. The idea of research in this aspect was inspired by the recent acts of terrorism in some leading educational institutions of Pakistan. University teachers were interviewed by the researcher. Questions asked by the researcher were developed from the relevant factors taken from respective literature. The researcher validated these questions with the expert opinion of his supervisor. After validation of questions of interview, data were collected from nine university teachers including three female and six male teachers, belonging to different universities of Pakistan. The sample was purpose drawn from teachers who belonged to different sects, castes, environment and culture, so that a comprehensive opinion come. The interview protocol followed all ethical considerations. The interviews recorded were translated into English with especial focus on the meanings. The collected data were then analyzed according to thematic description approach. The themes were identified and coded and then interpreted into meaningful answers to the research questions. Teachers believed that there were different types and nature of extremism in educational institutions. The major factors identified by the teachers were financial, power politics, deprivation of rights, over-ruling of merit, straying away from the true path of Islam and lack of economic opportunities. Teachers also suggested some recommendations for controlling extremism in universities of Pakistan